A prospective cohort study of adverse fetomaternal outcomes among overweight, obese, and normal weight pregnant women with term singleton pregnancy in a tertiary care hospital - Shyamal Dasgupta; Poulami Roy; Chiranjit Ghosh; Biswas, Jhuma; Pallabi Das; Utsa Ghosh; Avijit Pan; Swarnakamal Mondal (Asian Journal of Medical Sciences, 2022)
Background: Globally, overweight and obesity are the common risk factors with increasing frequency for adverse fetomaternal outcomes. In resource-poor countries, it is emerging as a threat for favorable pregnancy outcome even with the prevalence of high hunger index. Aims and Objectives: This study aims to determine the impact of obesity and overweight in pregnancy on fetomaternal outcomes in comparison to normal weight mothers. Materials and Methods: A prospective cohort study was conducted in a tertiary care center for 1½ years with singleton term pregnancies and 64 mothers with body mass index (BMI) ≥25 kg/m2 (cases) were compared with 64 normal weight mothers with BMI 18.5–24.9 kg/m2 (controls). Maternal and perinatal outcome was analyzed during antenatal, intranatal periods and after delivery along with the follow-up of newborns up to early neonatal period. Results: After optimizing the two groups in different sociodemographic status, the result shows significantly higher weight gain (P<0.001), incidence of gestational diabetes mellitus (P<0.001), hypertensive disorders of pregnancy (P<0.001), and macrosomia (P<0.001) in overweight and obese pregnant women than their normal weight counterparts. Increased cesarean section rate (P<0.001), postpartum hemorrhage (P<0.005), neonatal low Apgar score at 5 min (P<0.05), neonatal intensive care unit admission (P<0.05), and higher rate of early neonatal death were also observed in cases group than controls group. Conclusion: Pre-pregnancy intervention for optimization of maternal weight with proper surveillance of every pregnant mother of this subset and vigilant neonatal care may improve the obstetric and perinatal outcome.